Inclusive pedagogical practices in a rural and Mapuche intercultural school in Chile - Valenzuela Rettig, Pilar (2023)
This academic article corresponds to a case study on the problem of inclusive pedagogical practices from a Mapuche and rural perspective. The girls, boys and adolescents of this culture are at an educational disadvantage because they are not part of the normative population of Chilean citizenship. However, we identify educational institutions that generate inclusive practices contextualized to the territory, in search of a better education for the community. One of these is the rural school of Puquiñe Bajo, in the commune of Lanco, Región de los Ríos, Chile. The objective of the study was to analyze these practices in the school, with the purpose of achieving the inclusion in the Chilean school system of the student body from their Mapuche and rural identities. The approach is qualitative, descriptive, with the development of participant observation and interviews with teachers carried out during 2022. The results show the consolidated and collaborative development of the school community in terms of practices: implementation of intercultural seals in the Institutional Educational Project, giving relevance to the history of the territory, pedagogical work in and with Mapuche identity, collaborative work with families, curricular adjustments and Project-Based Learning and Cultural Research. Therefore, important data is presented to be considered in the pedagogical management processes in communities that have a background of rurality and ethnic origin. Also, these data are useful for research teams in intercultural and inclusive education, along with initial teacher training teachers to promote inclusive education.